ANALISIS HASIL BELAJAR DITINJAU DARI MOTIVASI BELAJAR PADA MATERI PEMANASAN GLOBAL - Wilhelmina, Alin Febrianti; Hadi, Wiwin Puspita; Tamam, Badrud; Yasir, Mochammad; Putera, Dwi Bagus Rendy Astid (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2023)
This study aims to determine learning outcomes, learning motivation, and student learning outcomes in terms of learning motivation on global warming material. The technique used as a data collection tool in this study is a test instrument used to measure learning outcomes, a questionnaire in the form of a Likert scale used to measure student learning motivation, and Pearson correlation test to determine the relationship between learning outcomes and learning motivation. In this study, the sample used was 125 seventh grade students at SMPN 1 Kepohbaru, Bojonegoro. The research variable consisted of two categories, namely the independent variable (learning motivation) and the dependent variable (learning outcomes). The results of the percentage of the average value of 72% are in the good category. Student learning outcomes in the very good category were 15 students (12%). In the good category 54 students (43.2%), in the sufficient category 42 students (33.6%), and in the 14 students category (11.2%). The results of the average percentage of learn-ing motivation that is 80.5% are in the high category. Students' learning motivation in the high category was 95 students (76%), in the medium category there were 30 students (24%) and in the low category 0 students (0%). Based on data analysis and research results as well as hypothesis testing that has been carried out, it is con-cluded that there is a positive and significant relationship between learning out-comes and learning motivation in seventh grade students of SMPN 1 Kepohbaru Bojonegoro. This means that the higher student learning outcomes, the higher the motivation to learn. With a correlation index of 1.165 with a t count of 21.642 and a coefficient of determination of 135.7%, it means that motivation contributes 135.7% to science learning outcomes while the rest is determined by other factors.